2019
DOI: 10.1177/1060028019886846
|View full text |Cite
|
Sign up to set email alerts
|

Are Clinical Outcomes Associated With Medication Regimen Complexity? A Systematic Review and Meta-analysis

Abstract: Background: Current evidence of the influence of the medication regimen complexity (MRC) on the patients’ clinical outcomes are not conclusive. Objective: To systematically and analytically assess the association between MRC measured by the Medication Regimen Complexity Index (MRCI) and clinical outcomes. Methods: A search was carried out in the databases Cochrane Library, LILACS, PubMed, Scopus, EMBASE, Open Thesis, and Web of Science to identify studies evaluating the association between MRC and clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…In a recent meta-analysis, the association between the degree of medication complexity and the clinical outcomes of hospitalisation, hospital readmission and medication non-adherence across different studies has been reported. 27 Furthermore, a recent systematic review on the medication adherence interventions highlighted the need to focus on the interventions that deemed to be effective to improve adherence such as medication regimen simplification, education and reminders. 28 However, to the author's knowledge, this is the first study that has assessed the impact of medicine regimen simplification strategies on medicine adherence and clinical outcomes in patients with long-term medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, the association between the degree of medication complexity and the clinical outcomes of hospitalisation, hospital readmission and medication non-adherence across different studies has been reported. 27 Furthermore, a recent systematic review on the medication adherence interventions highlighted the need to focus on the interventions that deemed to be effective to improve adherence such as medication regimen simplification, education and reminders. 28 However, to the author's knowledge, this is the first study that has assessed the impact of medicine regimen simplification strategies on medicine adherence and clinical outcomes in patients with long-term medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Defining MRCI cutoffs to categorize medication complexity may be dependent upon the studied population, based on previous MRCI studies. 4 , 8 , 10 - 12 Studies have been conducted in diverse populations, and there are no consistent cutoffs that define low and high complexity in the general population. For instance, 1 study 8 that evaluated the MRCI in defined populations with chronic disease (geriatric depression, human immunodeficiency virus, diabetes mellitus, and hypertension) found that the MRCI values for meeting complexity thresholds for high and low MRCI scores differed between disease-specific cohorts.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Additionally, impact of MRCI cutoffs on readmissions were either not reported or findings were not conclusive, limiting associations related to MRCI scores and readmission risk. 4 , 8 , 10 - 12 To our knowledge, only 1 study 4 has looked specifically at utilizing MRCI in psychiatric patients and found average MRCI scores of 17.62 and 19.36. The study focused on adults age 65 years or older with depression and, therefore, did not represent a nonelderly psychiatric population.…”
Section: Introductionmentioning
confidence: 99%
“…The dimensions with the worst assessment were Anxiety/Depression, Pain/discomfort and Self- The MRCI index is a validated 65-item tool that evaluates treatment regimen complexity based on the number of medications, dosage form, dosage frequency, and additional or special instructions. This index score ranges from 1.5 (for someone taking a single tablet or capsule taken once a day) to an undefined maximum since the score increases with the number of medications; greater scores indicate higher complexity [18]. Additionally, according to Morillo-Verdugo et al [19] a cut-off value of 11.25 for MRCI index score was employed for considering complex patient.…”
Section: Resultsmentioning
confidence: 99%